Multi-scale tilt depth estimation - Van Buren, Reece (My University, 2014)
Many an approach to the estimation of magnetic source depths from magnetic data has been investigated over the past half a century. These approaches have been shown to have particular strengths and weaknesses with few implemented on a wide scale, commercial basis. A review of many of the more popular, as well as a few of the more obscure methods, is presented within this work. The history of multi-scale computation, with emphasis on its application to potential fields is summarized. A newly developed depth estimation technique dubbed Multi-Scale Tilt Depth Estimation is offered. The method has been shown to derive suitable depth estimates when applied to modelled data computed from a range of simple synthetic models. Sensitivity of the method to model type, dip, interference and noise has been tested. A number of mitigating strategies to improve and stabilize the method’s performance have been proposed. Results of the successful application of the method to field datasets from the Bushveld Complex and surrounding areas in South Africa are shown. Code to execute the method, written in Matlab is offered in Appendix A. Figures of the application of the method to all synthetic models have been included in Appendix B and C. A portion of this work has been presented at the South African Geophysical Association’s 11th Biennial Technical Meeting and Exhibition in the form of verbal and poster presentations accompanied by a short paper which is included here in Appendix D.
Keywords: Multiscale modelling.